What’s in a Name? Defining Nurse Residencies to Design Evidence-based Programs - Sarah Yvonne Jimenez (European Scientific Journal, ESJ, 2021)
Nurse residencies are transition programs that support new graduate nurses as they begin their careers in clinical practice. Disparities among transition programs have made it difficult to compare outcomes and identify specific elements that contribute to overall effectiveness. The purpose of this paper is to propose a common nomenclature of nurse residencies to promote standardization across programs and to provide guidelines to assist staff development educators to create and implement comprehensive, costeffective, evidence-based programs.